Mental Health Rehabilitation of Post-Divorce Women: Reconstructing Islamic Family Law in a Contemporary Context - Iwannudin Iwannudin (Kuras Institute, 2024)
This study examines the rehabilitation of women’s mental health after divorce through the reconstruction of Islamic family law in a contemporary context. The main issue identified is the lack of attention to women’s psychological well-being in the practice of Islamic family law, despite the maqāṣid al-syarī‘ah emphasizing the protection of life (ḥifẓ al-nafs). The dominant formal legal paradigm tends to focus on the legality of marriage, divorce, child custody, and alimony without considering the post-divorce psychological impact, leaving women vulnerable to mental health risks, social stigma, and gender inequality. This study aims to reconstruct Islamic family law using a rehabilitative approach that integrates the principles of maqāṣid al-syarī‘ah and gender justice. A qualitative method with normative-empirical analysis was employed, reviewing Islamic legal sources, fiqh, the Compilation of Islamic Law (KHI), Marriage Law, court decisions, and in-depth interviews with judges, lawyers, and post-divorce women. Findings indicate that gender bias, patriarchy, and weak enforcement of substantive rights exacerbate mental vulnerability. A rehabilitation-based legal reconstruction provides psychological support, mental health-oriented mediation, and respect for women’s decisions, making Islamic family law more humane, gender-responsive, and consistent with maqāṣid al-syarī‘ah.